Peran Pemerintah dalam Meningkatkan Kesejahteraan Petani Salak di Desa Tinjoman Lama Kecamatan Padangsidimpuan Hutaimbaru Kota Padang Sidimpuan Tahun 2014 - Baskoro Wicaksono (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This research was conducted in the village of Tinjoman Lama District of Padangsidimpuan Hutaimbaru Padangsidimpuan City with three research question How are the government’s role in improving welfare of farmers in the village barking Tinjoman Lama? The purpose of this study to determine government’s role in improving the welfare of farmers in the village barking Tinjomam Lama District of Padangsidimpuan Hutaimbaru Padangsdimpuan City. This study is a descriptive quantitative research. The population in this study were all barking farmers in the village of Tinjoman Lama. The sample of this study a total of 36 respondents (50%) of the overall polpulations using random sampling technique, that is by knowing all the farmers barking then randomized based on the name for the next interview. To collect the data the researchers use methods of document , observation and interview by using the interview guide as a reference to obtain information in analyzing the research data used quantitative analysis and descriptive described. Based on the study concluded lack of government’s role in improving the welfare of farmers bark that can be seen from the absence of assistance in the form of marketing, production quality improvement, education / training in agriculture, provision of quality seeds and fertilizers or appropriate technology.